The endo-aza-Michael addition in the synthesis of piperidines and pyrrolidines - Bates, Roderick Wayland (2020)
Intramolecular endo-aza-Michael additions are categorised in various ways. Firstly whether they are single or double reactions, secondly whether they are endo- or exo-activated (or both), thirdly whether the Michael acceptor is an alkene or an alkyne, and finally whether the product is a six or a five membered ring. Reactions in the various categories are illustrated by syntheses of piperidines and pyrrolidines, including a range of natural products. The question of the stereochemical outcome and whether it is understood is discussed.